Investigation of heat transfer in a revolving vane compressor chamber - Lew, Samuel Bingheng. (2009)
The outcome of the research work done by the author on the operations of the revolving vane compressor is described in this final year project report. The main objective of this project was to study the convection heat transfer during the compression process in the chamber of a revolving vane compressor.